2022
DOI: 10.1016/j.xplc.2021.100273
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-like protein kinases in plant reproduction: Current understanding and future perspectives

Abstract: Reproduction is a crucial process in the life span of flowering plants, and directly affects human basic requirements in agriculture, such as grain yield and quality. Typical receptor-like protein kinases (RLKs) are a large family of membrane proteins sensing extracellular signals to regulate plant growth, development, and stress responses. In Arabidopsis thaliana and other plant species, RLK-mediated signaling pathways play essential roles in regulating the reproductive process by sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 203 publications
(398 reference statements)
0
19
0
Order By: Relevance
“…How the EPFL signals are transduced to control integument morphogenesis after they are perceived by ERf receptors is another important question. A SERK or CIK coreceptor is often recruited by a ligand‐binding RLK with long extracellular domain to fully activate the signaling pathways (Gou & Li, 2020; Cui et al ., 2022). It was noticed that serk1/2/3 mutants were female‐sterile (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…How the EPFL signals are transduced to control integument morphogenesis after they are perceived by ERf receptors is another important question. A SERK or CIK coreceptor is often recruited by a ligand‐binding RLK with long extracellular domain to fully activate the signaling pathways (Gou & Li, 2020; Cui et al ., 2022). It was noticed that serk1/2/3 mutants were female‐sterile (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AGP24 co-expression data showed some interesting genes from other gene families that are important for plant reproduction such as RECEPTOR-LIKE SERINE/THREONINE KINASE 2 (RKF2; AT1G19090) or CRK1 (CYSTEINE-RICH RLK) and CALCIUM-DEPENDENT PROTEIN KINASE 26 (ATCPK26; AT4G38230), belonging to the calcium-dependent protein kinases family (Ca 2+ /CPKs), vital components in the Ca 2+ signaling pathways. Receptor-like protein kinases (RLKs) are a large family of membrane proteins essential for reproductive development (Cui et al, 2022), and Ca 2+ is described as an important ion in the entire reproductive process and has also been related to the putative functions and mode of action of AGPs (Cheng et al, 2002;Lamport and Vaŕnai, 2013). A recent study clearly highlighted AGPs as essential players involved in novel molecular pinball machines of the plasma membrane controlling cytosolic Ca 2+ levels that regulate plant metabolism (Lamport et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Glysoja.15G042020 and Glysoja.15G042019, which encode Glutathione Stransferase, were detected in the 48099201-48129356 region on chromosomes 15. A number of studies have reported that Glutathione S-transferase, caffeoyl-CoA O-methyltransferase, LRR receptor-like serine/threonine protein kinase, and receptor-like protein kinases play important roles in plant defense-related reactions against fungal attacks [43][44][45][46][47][48]. Jing et al (2015) found that the expression of the GST family in soybeans was down-regulated following P. sojae infections [49].…”
Section: Discussionmentioning
confidence: 99%